Liberalism undressed - Lieberman, Jethro Koller (Oxford : Oxford University Press, 2013)
During the past 40 years, many of liberalism's most distinguished defenders have presented complex, controversial, abstruse, and even impenetrable theories to justify liberal institutions and practices, often relying on metaphysical constructs, imaginary beings, and fanciful events to describe abstract liberal principles that rarely reach real-world problems. This book proposes that John Stuart Mill's harm principle - that the state may act only to prevent harm to others - can justify a government capable of dealing with pressing modern problems of human harm while restrained enough to provide people freedom to live life on their own terms.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Liberalism